PERANAN ORANG TUA DALAM MENINGKATKAN PRESTASI BELAJAR ANAK - Afni, Nur; Jumahir, Jumahir (Pusat Studi Gender dan Anak, IAIN Palu, 2020)
Family is the main educational media for student development, in order to develop their potential both physically and spiritually by optimizing family's environment role as an educational environment. Some of these roles are as follows: paying attention to students' progress, engaging in learning activities, creating a learning atmosphere, providing learning guidance, and providing learning motivation to students. Learning achievement is students’ ability to achieve certain subjects matter according to the curriculum, time, and certain criteria. Student's learning achievement is affected by various factors from outside themselves (external). The achievements are essentially the results of interactions with their environment, which are family environment and school environment as the education center.